An appraisal of the socio-legal implications of population growth on the environment (2013)
Year in year out, population has continued to be on the increase throughout the world. The rise in population is due to several factors some of which are low mortality rate, improved medical and technology apparatus, industrialization, improved economy, fall in death rates and urbanization amongst others. However, population growth has continued to take its toll on the environment and other natural resources in the planet earth. Hence, the fear now is whether, due to the population growth, the carrying capacity of the environment will be able to sustain the trend. The thrust of this paper is, therefore, to appraise the socio-legal impact of the population growth on the environment. In doing this, the paper discusses various factors that contribute to population growth and the effect of popidation generally on the environment. The paper concludes with few suggestions to stem the tide of population growth globally.